A Igreja Messiânica Mundial do Brasil : o sistema de prestações e contraprestações no Johrei em Sergipe - Bomfim, Jorge (2021)
This work aims to analyze the service systems in the religious practices of the World Messianic Church of Brazil (IMMB), specifically in the religious field in Sergipe. The religious field in Sergipe reflected the trend of reconfiguration of religious forms on the national scene that began in the 20th century, a time when a plurality of beliefs, religiosities and religious institutions emerged in this society, which the Social Sciences classify as New Religious Movements (NMR). In this dissertation we evaluate the doctrinal elements of this institution, contained in the teachings and liturgical ceremonial practices and their applicability within its membership, in addition to the symbolic exchange relationships in its religious activities, especially in the act of Johrei, which constitutes the formal object of inquiry . Our greatest interest was understood the flows of symbolic exchanges, discussed in the third chapter of this article, what the agents who apply and receive this act of faith intend and how the systems of benefits and considerations in this ritual practice of the IMMB are processed and highlighted. Methodologically, at first, a bibliographic survey was carried out on the history and constitution of the IMMB, then the field research was carried out, where we analyzed this community and the exchange system in the Johrei Act. For this, we established a descriptive procedure with a qualitative approach and used the ethnographic method, in addition to conducting a pre-structured choice by sampling priests, adherents, members and former members, seeking answers to the questions existing in the hypothesis and objectives unique to this analysis. We examined scientific theories relating the data started in legal, teachings, religious experiences and reporting in order to verify the phenomenon addressed, a conjecture discussed and confirmed at the end of this work, when we found elements of symbolic exchanges in the act of Johrei of IMMB.